KARAKTER RELIGIUS PEMBELAJARAN IPA - Susilawati Susilawati (Jurnal Pendidikan Islam, 2012)
Character education as one of the national development priorities in 2010 must be coherent are in line with the national education goals. Expected character education is not a subject that stands alone or is a value that is taught, but rather the effort to plant one of these values through the integration of subjects. Learning science in elementary school specifically aims to develop knowledge, attitudes and skills with the main objective to develop creativity and critical thinking. Values that can be implanted through a process of habituation in science subjects in primary schools are religious, honest, tolerance, discipline, hard work, creative, independent, democratic, curiosity, the spirit of nationalism, patriotism, recognize excellence, friendship/communicative, love peace, love reading, environmental care, social care, and responsibility. Aspects must be considered in the integration is to link these values explicitly in planning, implementing and assessing learning lessons tailored to the characteristics of the subjects.